The Role of Mindfulness and Positive Body Image in Predicting Physical Activity Among Sports-Involved University Students (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Previous research suggests that negative body image may decrease physical activity (PA), whereas positive body image may increase participation in PA. Mindfulness during PA (mindful monitoring and acceptance of body and mind) is associated with more positive body image. This study examined how mindfulness during PA and body appreciation are related to PA in a sample of students.Methods: The study employed a cross-sectional design with 539 university and college students from Lithuania involved in organised, recreational sports or home exercise with a mean age of 23.3 ± 7.2 years (49.7% were women). Participants completed an online survey assessing sociodemographic data, PA levels (Godin Leisure-Time Exercise Questionnaire), mindfulness during PA (State Mindfulness Scale for Physical Activity 2, SMS-PA-2, consisting of four subscales: Monitoring and Accepting Body and Mind), and body appreciation (Body Appreciation Scale 2, BAS-2). Statistical analyses included Pearson correlations and linear regression modelling. The study was approved by the Social Research Ethics Committee (Protocol No. SMTEK-131, LSU), and participants provided informed consent.Results: Small but significant correlations between SMS-PA-2 subscales, BAS-2, and PA were observed in male and female students. In the multivariate linear regression model of female students, accepting mind (β = 0.14, p = 0.033) and monitoring body (β = 0.16, p = 0.030) during PA positively predicted PA, while body appreciation had no significant effect. In males, body appreciation (β = 0.17 and β = 0.22, p < 0.05) but not mindfulness during exercise was positively associated with PA. Both models were controlled for body mass index.Conclusion: This study highlights the role of mindfulness and body appreciation in predicting PA among higher-education students. For females, mindful awareness during exercise positively predicts PA, while for males, body appreciation plays a key role. These findings suggest that integrating mindfulness practices and fostering body appreciation in sports programmes may enhance engagement in PA across genders.Support/Funding Source: This study was funded by the Research Council of Lithuanian (Grant No. S-MIP-22-25).